Comparison of different platelet count thresholds to guide administration of prophylactic platelet transfusion for preventing bleeding in patients with haematological disorders after chemotherapy or stem cell transplantation (protocol) - Estcourt, L; Doree, C; Trivella, M; Hopewell, S; Murphy, M; Tinmouth, A (John Wiley and Sons, Ltd, 2014)
This is the protocol for a review and there is no abstract. The objectives are as follows: To determine whether different platelet transfusion thresholds for administration of prophylactic platelet transfusions (platelet transfusions given to prevent bleeding) affect the efficacy and safety of prophylactic platelet transfusions in preventing bleeding in patients with haematological disorders after chemotherapy with or without stem cell transplantation.